Targeted Knockdown of Hepatic SOAT2 With Antisense Oligonucleotides Stabilizes Atherosclerotic Plaque in ApoB100-only LDLr−/− Mice. Issue 9 (September 2015) - Melchior, John T.; Olson, John D.; Kelley, Kathryn L.; Wilson, Martha D.; Sawyer, Janet K.; Link, Kerry M.; Rudel, Lawrence L.
Abstract : Objective—: To test the hypothesis that the attenuation of cholesterol oleate packaging into apoB-containing lipoproteins will arrest progression of pre-existing atherosclerotic lesions. Approach and Results—: Atherosclerosis was induced in apoB-100 only, LDLr –/– mice by feeding a diet enriched in cis -monounsaturated fatty acids for 24 weeks. A subset of mice was then euthanized to quantify the extent of atherosclerosis. The remaining mice were continued on the same diet (controls) or assigned to the following treatments for 16 weeks: (1) a diet enriched in n-3 polyunsaturated fatty acids, (2) the cis -monounsaturated fatty acid diet plus biweekly injections of an antisense oligonucleotide specific to hepatic sterol-O-acyltransferase 2 (SOAT2); or (3) the cis -monounsaturated fatty acid diet and biweekly injections of a nontargeting hepatic antisense oligonucleotide. Extent of atherosclerotic lesions in the aorta was monitored morphometrically in vivo with magnetic resonance imaging and ex vivo histologically and immunochemically. Hepatic knockdown of SOAT2 via antisense oligonucleotide treatment arrested lesion growth and stabilized lesions. Conclusions—: Hepatic knockdown of SOAT2 in apoB100-only, LDLr –/– mice resulted in remodeling of aortic atherosclerotic lesions into a stable phenotype, suggesting SOAT2 is a viable target for the treatment of atherosclerosis. Abstract : Supplemental Digital Content is available in the text.